2018
DOI: 10.1021/acs.inorgchem.8b01821
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Density Functional Methods for Calculation of State Energies of First Row Spin-Crossover Molecules

Abstract: A systematic study of the performance of several density functional methodologies to study spin-crossover (SCO) on first row transition metal complexes is reported. All functionals have been tested against several mononuclear systems containing first row transition metal complexes and exhibiting spin-crossover. Among the tested functionals, the hybrid meta-GGA functional TPSSh with a triple-z basis set including polarization functions on all atoms provides with the best results across different metals and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 104 publications
10
126
0
Order By: Relevance
“…Single‐molecule DFT calculations were reported in many cases together with IR, Raman, and NIS spectra collected in the two spin states, while some Raman and isotope‐substituted IR data were taken from earlier works . Other works focused more specifically on spin state energetics and DFT methodology improvements . The [Fe(phen) 2 (NCS) 2 ] molecule consists of 51 atoms, which give rise thus to 147 fundamental vibrational modes.…”
Section: Vibrational Spectramentioning
confidence: 99%
“…Single‐molecule DFT calculations were reported in many cases together with IR, Raman, and NIS spectra collected in the two spin states, while some Raman and isotope‐substituted IR data were taken from earlier works . Other works focused more specifically on spin state energetics and DFT methodology improvements . The [Fe(phen) 2 (NCS) 2 ] molecule consists of 51 atoms, which give rise thus to 147 fundamental vibrational modes.…”
Section: Vibrational Spectramentioning
confidence: 99%
“…[11][12][13][14] Extensive effort has therefore been devoted to evaluate different quantum chemical approaches for spin-state energetics and numerous studies on Fe(II), Fe(III) and Co(II) species have been reported. [15][16][17][18][19][20][21][22][23][24][25] Recent examples include the 2017 study by Pierloot et al into the performance of CASPT2 and NEVPT2 to describe the spin-state energetics of TM ions, TM ions surrounded by point-charges, and a range of first-row TM complexes, 16 and Radoń's 2019 assessment of CCSD(T), CASPT2, NEVPT2, MRCI and DFT for the calculation of experimental spin-state data for four octahedral Fe(II) and Fe(III) complexes. 20 Additionally, density matrix renormalization group (DMRG) methods have found increasing use in the study of spin-state energetics of first-row TM complexes, particularly for systems where the TM centres are situated within extensively conjugated ligands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Still, there is no magic number for the exact exchange admixture and the best compromise for a given type of system depends on other features of the functional. Although the popular B3LYP hybrid functional (20% HF exchange) [44,45] has been used with reasonably good results, the hybrid-meta-GGA TPSSh functional (10% HF exchange) [46] is a better and more widely validated choice, not only for exchange coupling constants but for a range of molecular properties [34,[47][48][49][50]. This choice of functional is not necessarily transferable, as demonstrated for example by the fact that TPSSh is no longer at the methodological sweet spot for the calculation of exchange coupling constants even for complexes of metal ions isoelectronic with manganese [51].…”
Section: Introductionmentioning
confidence: 99%